THE E-BUSINESS COMMUNITY MODEL IS USED TO IMPROVE COMMUNICATION BETWEEN BUSINESSES BY UTILIZING UNION PRINCIPLES - Fauzi, Fauzi; Al-Khowarizmi, Al-Khowarizmi; Muhathir, Muhathir (JITE (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING), 2020)
Business is an interpersonal and organizational activity that involves the process of selling, purchasing both goods and services with the aim of making a profit. But to get a large profit, it takes many partners who have a high desire to move forward. Information technology provides services for business people so that media information is available as a sign of obstacles. In addition it is necessary to do modeling where the process of communication between businesses running on information technology has a different profit from the business being run. Thus the union has the principle of kinship and has the principle of profitability divided by the amount of contribution given so that the creation of a model in electronic business (e-business) in the hope of having a family principle that is able to provide special profits for businesses other than the profits that run on certain businesses.